Contribution of TRPA1 as a Downstream Signal of Proteinase-Activated Receptor-2 to Pancreatic Pain - Yuka Terada; Mayuko Fujimura; Sachiyo Nishimura; Maho Tsubota; Fumiko Sekiguchi; Hiroyuki Nishikawa; Atsufumi Kawabata (Elsevier, 2013)
We examined if TRPA1, like TRPV1, contributes to pancreatic nociceptor excitation following proteinase-activated receptor-2 (PAR2) stimulation and to pancreatitis-related pain in mice. A PAR2-activating peptide, infused into the pancreatic duct, caused spinal Fos expression, which was prevented by AP18, a TRPA1 inhibitor. Repeated administration of cerulein caused referred hyperalgesia accompanying pancreatitis, which was reversed by SB366791, a TRPV1 inhibitor, but not AP18. AP18, administered in combination with a subeffective dose of SB366791, significantly suppressed the referred hyperalgesia. Our findings suggest that TRPA1, like TRPV1, mediates PAR2-triggered pancreatic nociception and that TRPA1 in collaboration with TRPV1 latently contributes to pancreatitis-related pain. Keywords:: transient receptor potential ankyrin-1 (TRPA1), proteinase-activated receptor-2 (PAR2), pancreatic pain